LEGAL CONSEQUENCES OF REGISTERING A TRADEMARK UNDER A PERSONAL NAME IN A LIMITED LIABILITY COMPANY - Asfarina Kurniawati; Eko Wahyudi (JOSAR (Journal of Students Academic Research), 2023)
Problems with the application of law in society are indicated by the existence of the GOOD DAY trademark dispute between PT Santos Jaya Abadi and Soedomo Mergonoto as the director of PT Santos. In the GOOD DAY brand dispute, the judge handed down a decision to reject the plaintiff entirely at first instance and cassation. The aim of the study was to analyze the judge's considerations in the decision Number 722 K/Pdt.Sus-HKI/2015 and the legal consequences arising from registering a mark with an individual's name for legal entities in a limited liability company. In conducting research, using normative juridical research methods, because normative juridical focuses on legislation and literature that is relevant to the case under study. The data analysis method used is qualitative analysis. The results of the study show that the verdict handed down by the judge in decision Number 722 K/Pdt.Sus-HKI/2015 is contrary to the principle of separation of assets, especially contained in Law Number 40 of 2007 concerning Limited Liability Companies. The defendant, namely Soedomo Mergonoto, in registering the GOOD DAY brand which had been developed and promoted with funds from PT Santos Jaya Abadi under the personal name of the directors, the actions of the directors showed bad faith. The legal consequence is that there is an exclusive right attached to Soedomo Mergonoto due to trademark registration, while PT Santos Jaya Abadi does not have exclusive trademark rights.